The Effectiveness of Surgeon Decision on Pain Syndrome of Pelvic Origin Treatment in Women Estimated with the Model of Decision Tree - Buzynovsky, А.B.; Kоvalenko, О.S.; Bayazitov, N.R.; Godlevsky, L.S. (Кибернетика и вычислительная техника, 2018)
The purpose of the work is to investigate the effectiveness of different methods of treatment women with pain syndrome originated from pelvis and lower part of abdomen on the basis of retrospective analysis of 1092 histories of diseases during 2013–2017 р.р., Results. It was established that the probability of complete health restoration was 0,83 after surgical treatment and 0,62 after drug treatment. In case of initial inefficiency of drug treatment the probability of restoration of health as a result of surgical intervention was 0,40. The EPT in surgically treated patients was less than EPT in patients with therapeutic treatment by 3,29 times at the moment of making decision on the method of treatment. Мета роботи полягає у порівнянні ефективності різних методів лікування жінок з больовим синдромом мискового походження на основі ретроспективного аналізу 1092 історій хвороб пацієнтів, яким лікування було надано в період 2013–2017 р.р. Результати дослідження. Встановлено, що імовірність повного відновлення здоров’я склала 0,83 після хірургічного і 0,62 після консервативного лікування. У випадку, коли первинне консервативне лікування не приводило до одужання, імовірність одужання після проведення хірургічного втручання дорівнювала 0,40. Ефективність періоду лікування, розрахована для пацієнтів з первинним хірургічним лікуванням, була менша в 3,29 разу у порівнянні з ефективністю, розрахованої для пацієнтів з первинним консервативним лікуванням. Проведены ретроспективные исследования эффективности принятия решений при диагностике и лечении пациентов хирургического профиля — женщин, страдаючих хроническим болевым синдромом. Результаты анализа историй болезни 1092 пациенток, которым была оказана врачебная помощь в период 2013–2017 г.г., проведенного на основе построения дерева решений, показали, что вероятность выздоровления при проведении хирургического вмешательства составила 0,83, в то время как при проведении медикаментозного лечения — 0,62. В случае неэффективности медикаментозного лечения вероятность выздоровления уменьшалась до 0,40. Определены ключевые моменты применения системы поддержки решений хирурга, позволяющие повысить эффективность лечения данной категории пациентов.